Haptic Stabilization of Posture in Adults With Intellectual Disabilities Using a Nonrigid Tool - Mauerberg-deCastro, Eliane [UNESP]; Lucena, Carmila Souza [UNESP]; Cuba, Bruna W. [UNESP]; Boni, Rosana C. [UNESP]; Campbell, Debra Frances; Moraes, Renato (Human Kinetics Publ Inc, 2010)
This study assessed the effects of haptic information on the postural control systems of individuals with intellectual disabilities (ID), through the use of a nonrigid tool that we call the anchor system (e.g., ropes attached to graduated weights that rest on the floor). Eleven participants with ID were asked to stand, blindfolded, on a balance beam placed at two heights (10 and 20 cm), for 30 s, while using the anchor system at two weights. The lighter anchor weight appeared to improve the individuals' balance in contrast to a control task condition; therefore, we concluded that haptic sensitivity was more significant in helping to orient the body than was the anchor's mechanical support alone.